Analysis of 39 cyanobacterial species reveals rbcx subunit to be present between L and S Subunits - Mehrotra, Rajesh; Siddhu, Gurpreet Kaur; Rashmi, Mis.; Mehrotra, Rajesh; Mehrotra, Sandhya (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
The impact of greater oxidation event on RuBisCo has been tremendous. It has led to the competition between carbon dioxide and oxygen at the active site the enzyme. Cyanobacteria developed strategies to combat this change by concentrating carbon dioxide in organelles called carboxysomes. RbCx helps in proper folding of RuBisCO by interacting with Rbcl. However, it is not an absolute requirement for RuBbisCO to attain proper folding only with the aid of RbCx. RbCx has a chaperone like activity. The present analysis led to the finding that in case of cyanobacterial species lacking RbCx contains multitude of protein showing homology to chaperone like proteins. These proteins might be playing the same role as RbCx in these cyanobacterial species to help RuBisCo acquiring proper folding. Analyses also indicated that in general the rbcx motif to be present between rbcl and rbcs.